An audit of prescriptions in general medicine outpatient department in a tertiary care government hospital in Eastern India: a quality improvement project - ., Luv; ., Ravikirti; Biswas, Ratnadeep; Ojha, Vishnu S. (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Prescriptions are an important link between physicians and patients. Any medication therapy can become ineffective if not communicated properly to the pharmacist and patient. Therefore, it’s important to maintain the quality of prescription-writing. Thus, we conducted a prescription audit in a tertiary-care hospital. Methods: 413 prescriptions having 1683 drugs were selected by convenience sampling. Adherence to 4 quality parameters, namely mention of date, allergy status, date of next visit, and whether or not the prescription was signed legibly, were observed for each prescription. 5 parameters viz. whether or not the drug was written in capital letters, whether the generic name of the drug was mentioned, and prescription of drug schedule, dose, and duration were evaluated for each drug separately. Frequency tables and appropriate bar plots were created. Results: Dates were mentioned in all prescriptions. There were 4.07±0.44 (mean±SD) drugs per prescription. Using capital letters and generic names was observed for 12% and 21% of the drugs. Dose, duration, and schedule were written for 51.4%, 98.6% & 98.7% drugs respectively. The next visit was mentioned in 61.7% cases. 21.8% prescriptions were signed legibly and only 0.5% prescriptions had allergy status. Conclusions: A significant scope of improvement was observed in signing the prescription legibly, mentioning next visit, using generic names, writing the drug names in capital letters, drug doses, and mentioning allergy status. Conducting regular audit-feedback-audit loops will improve the quality of health care delivery in a practical manner.